Sustainable Smart Cities and Energy Management: The Labor Market Perspective - Olga Pilipczuk (Energies, 2020)
Nowadays, sustainability is one of the strategic goals of smart cities. They are the essential solution to creating the sustainable future. On the other hand, the smart city is intended to deal with the problems of energy management. This paper examines the influence of the smart sustainable cities concept on energy management from the labor market perspective. The paper fulfills the research gap about energy manager profession transformation considering smart sustainable city concept. The aim of the paper is to create an up-to-date holistic energy manager skill model with a focus on emerging technologies. The skill model reflects the synergy of two methodological approaches: the theoretical and practical approaches. Descriptive statistics are used to present the labor market research results. It is concluded that the core elements of the smart sustainable city concept have an impact on energy management are sustainability and big data. The labor market research also draws differences in the amount and structure of demand on energy manager skills by countries, but at the same time similar skills requirements are found. The skill model of the energy manager profession is built around several main groups associated with specific knowledge, social skills, and behavior skills. The findings of the present research can contribute to knowledge and practice by applying it in the process of developing energy manager competency models in commercial and non-commercial enterprises as well as in education programs and training courses.